Efektifitas Penambahan Probiotik Dosis Berbeda pada Pertumbuhan Ikan Lele (Clarias sp.) di UPR Mitra Mina Sejahtera - Barus, Clara Claresta; Himanah, Hafiz; Mahira, Arika; Aulia Sari, Della; Cristina, Nena; Tyas, Dwi Ayuning; Yonarta, Danang (Seminar Nasional Lahan Suboptimal, 2023)
Barus, C.C., Himanah, H., Mahira, A., Sari, D.A., Cristina, N., Tyas, D.A., & Yonarta, D. (2023). Effectiveness of adding different doses of probiotics on the growth of catfish (Clarias sp.) at UPR Mitra Mina Sejahtera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 145-150).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of the problems experienced by fish farmers is that the price of the feed ingredients used is increasingly high and difficult to find. Therefore there needs to be a solution to overcome the problems with commercial feed by using the addition of probiotic feed to make it more efficient for the survival of catfish. The aimed of this research was to determine the effect of adding probiotics at different doses on the growth of catfish. The research procedures used in this research are preparing of fish ponds, adding probiotics to feed and rearing of fish. This maintenance uses 2 ponds of cement with a size of 1,5×1,5× L-1 m3 using 2 treatments with different doses, P1 is 10 ml kg-1 and p2 is 15 ml kg-1. The parameters observed in this study were absolute growth of length and weight, Feed Efficiency, survival rate and water quality. In this study, the absolute growth results of fish in P2 were higher than P1. During catfish rearing, it was found that the Feed Efficiency in P2 was lower than P1, which indicated that the conversion of feed in P2 was more efficient in being converted into meat. Fish survival obtained in P2 was also higher than in P1. Water quality (temperature, pH, dissolved oxygen and ammonia) during fish rearing was more optimal at P2 than P1. Based on the results of the research data obtained, the best dose of probiotics that accelerated growth occurred at P2 with 15 ml kg-1compared to P1 with 10 ml kg-1.